Tantangan Penggunaan M-Learning Mahasiswa Universitas Sains Al-Qur’an Wonosobo - Dian Asmarajati (Universitas Sebelas Maret, 2019)
The fact that students have mobile technology does not mean they use it for their academic activities. This research aims to discover what students do with their mobile devices? What guidance did they receive from their lecturers at the university? This research answers are built from a theoretical framework and involves collecting data from samples. For example, problems such as the ability to manage time and learning activities, what students know about technology, what activities they do with it, or what they have learned about it in the context of school education. This study is an analysis of social phenomena. Construction data techniques were chosen so as to enable students to express their own assumptions and analyze their social practices such as semi-open surveys of students, semi-structured interviews with faculty and focus groups with students. All information obtained is then triangulated. It was found that they used their mobile devices even though there were no instructions from their lecturers. Although departing audiovisual has turned into a favorite tool of young people to try to gather information, it turns out students do not make it a choice for learning. Therefore this has become an opportunity to promote the use of mobile technology for academic purposes